Zinc supplementation for the prevention of type 2 diabetes mellitus in adults with insulin resistance - El Dib, Regina [UNESP]; Gameiro, Orsi L. F. [UNESP]; Ogata, Matheus S. P. [UNESP]; Modolo, Norma S. P. [UNESP]; Braz, Leandro Gobbo [UNESP]; Jorge, Eliane C. [UNESP]; Nascimento Junior, Paulo do [UNESP]; Beletate, Vânia (Wiley-Blackwell, 2015)
BackgroundDiabetes is associated with long-term damage, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, heart and blood vessels. The risk of developing type 2 diabetes increases with age, obesity and lack of physical activity. Insulin resistance is a fundamental aspect of the aetiology of type 2 diabetes. Insulin resistance has been shown to be associated with atherosclerosis, dyslipidaemia, glucose intolerance, hyperuricaemia, hypertension and polycystic ovary syndrome. The mineral zinc plays a key role in the synthesis and action of insulin, both physiologically and in diabetes mellitus. Zinc seems to stimulate insulin action and insulin receptor tyrosine kinase activity.ObjectivesTo assess the effects of zinc supplementation for the prevention of type 2 diabetes mellitus in adults with insulin resistance.Search methodsThis review is an update of a previous Cochrane systematic review published in 2007. We searched the Cochrane Library (2015, Issue 3), MEDLINE, EMBASE, LILACS and the ICTRP trial register (frominception toMarch 2015). There were no language restrictions. We conducted citation searches and screened reference lists of included studies.Selection criteriaWe included studies if they had a randomised or quasi-randomised design and if they investigated zinc supplementation compared with placebo or no intervention in adults with insulin resistance living in the community.Data collection and analysisTwo review authors selected relevant trials, assessed risk of bias and extracted data.Main resultsWe included three trials with a total of 128 participants in this review. The duration of zinc supplementation ranged between four and 12 weeks. Risk of bias was unclear for most studies regarding selection bias (random sequence generation, allocation concealment) and detection bias (blinding of outcome assessment). No study reported on our key outcome measures (incidence of type 2 diabetes mellitus, adverse events, health-related quality of life, all-cause mortality, diabetic complications, socioeconomic effects). Evaluation of insulin resistance as measured by the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) showed neutral effects when comparing zinc supplementation with control (two trials; 114 participants). There were neutral effects for trials comparing zinc supplementation with placebo for total cholesterol, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol and triglycerides (2 studies, 70 participants). The one trial comparing zinc supplementation with exercise also showed neutral effects for total cholesterol, HDL and LDL cholesterol, and a mean difference in triglycerides of -30 mg/dL (95% confidence interval (CI) -49 to -10) in favour of zinc supplementation (53 participants). Various surrogate laboratory parameters were also analysed in the included trials.Authors'conclusionsThere is currently no evidence on which to base the use of zinc supplementation for the prevention of type 2 diabetes mellitus. Future trials should investigate patient-important outcome measures such as incidence of type 2 diabetes mellitus, health-related quality of life, diabetic complications, all-cause mortality and socioeconomic effects.
Keywords: Dietary Supplements; Diabetes Mellitus, Type 2 [prevention &control]; Zinc [administration &dosage]; Humans